GENERAL ELECTIONS IN INDONESIA FROM THE PANCASILA PERSPECTIVE - Muhammad Alvhin Assyidhiqi (JURNAL SETIA PANCASILA, 2024)
Indonesia is a democratic country that obliges its implementation to adhere to the values stipulated in Pancasila and the 1945 Constitution as the foundation of the state. The principle of popular sovereignty, which is embedded in the fourth Sila of Pancasila, creates a concept known as people's sovereignty, where the people are the ultimate holders of sovereignty and have rights and responsibilities in the governance of the state. General elections (Pemilu) are an expression of these democratic values and a manifestation of the principle of people's sovereignty in the Indonesian democracy system. This research aims to delve deeper into the implementation of Pemilu from a Pancasila perspective. The research method used is qualitative, where the researcher collects data from various sources such as books, journals, and other relevant references related to the research topic. The research concludes that Pemilu in Indonesia is an implementation of democracy rooted in the values of Pancasila and upholds the principle of people's sovereignty as outlined in Pancasila as the foundation of the state. However, in the current era, the implementation of Pemilu still falls short of the ideal Pancasila and is not entirely sufficient in realizing the principle of people's sovereignty.